Mekanisme Pengelolaan Utang Negara dan Implikasinya terhadap Perekonomian Nasional - Dewi Yanti; Junita Mawartina; Heti Sarlini; Wahjoe Pangestoeti (Jurnal Hukum, Administrasi Publik dan Negara, 2025)
The mechanism of state debt management is a process involving fiscal and monetary policies to regulate the issuance, use, and repayment of state debt. In its management, the government usually uses instruments such as bonds, bilateral loans, and multilateral loans to finance the budget deficit. State debt can be used to fund infrastructure projects, health, education, and other important sectors, but its management must be careful so as not to burden the economy. One important aspect of debt management is maintaining the debt ratio to Gross Domestic Product (GDP) so that it remains under control. If state debt increases significantly without being balanced by economic growth, it can pose a risk of inflation, a larger budget deficit, and a reduction in market confidence in the government's ability to repay debt. On the other hand, good debt management can encourage economic growth by financing productive projects that increase competitiveness and public welfare. Strict supervision of debt allocation and transparency in the use of funds are essential to avoid misuse and increase the effectiveness of debt management. In addition, the role of international institutions such as the IMF and the World Bank is also crucial in providing technical advice and support for sustainable debt management policies.